A new species of Cornucistela Campbell, 1980 (Coleoptera: Tenebrionidae: Alleculinae: Gonoderina) from Iran - Novák, Vladimír; Nabozhenko, Maxim Yu. (Zootaxa, 2019)
A second species of the previously monotypic genus Cornucistela (C. anichtchenkoi sp. nov.) is described, illustrated and compared with C. serrata Campbell, 1980 (type species). It is a first record of the genus in Iran (South Khorasan Province).